PENGARUH KADAR HB DAN LINGKAR LENGAN ATAS (LILA) PADA IBU HAMIL TRIMESTER III TERHADAP BERAT BADAN LAHIR BAYI DI PUSKESMAS WILAYAH KABUPATEN BANYUMAS - Happinasari, Ossie; Suryandari, Artathi Eka (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2015)
Hemoglobin levels and Upper Arm Circumference is a biochemical indicator to determine the nutritional status of pregnant women. World Health Organization recommends ideal hemoglobin level of maternal is â‰¥ 11 g / dl. High or low hemoglobin levels and lack of LILA during pregnancy has an effect on birth weight because it can lead to impaired fetal growth in the womb. Objective: to identify the influence of Hb and LILA at the mother to birth weight. Survey with a cross sectional approach. Population research is all three trimesters pregnant women. Samples were determined by simple random sampling technique, a large sample is 225. The analysis of this study is the univariate analysis using frequency distribution, bivariate analysis using chi square test. Results: The majority of Hb levels in pregnant women results are not normal number of 145 respondents (64.4%). The majority of pregnant women LILA normal number of 169 participants (75.1%). There is no correlation Hb pregnant women with birth weight infants (p-value = 0.723). There is no correlation LILA with birth weight infants (p-value = 0.051). Keywords: Hb, LILA, Pregnancy, Birth Weight Infants